Left atrial strain reveals subclinical dysfunction in children after successful coarctation repair - Thuy Thuc Minh Pham; Phuc Nang Vu; Chi Thi Khanh Nguyen; Hung Quoc Nguyen; Thu-Tinh Nguyen; Phuc Minh Vu (PLoS ONE, 2026)
Background Although surgical repair of aortic coarctation (CoA) often restores hemodynamic integrity, subclinical myocardial dysfunction may persist long-term. Left atrial (LA) strain is a sensitive marker of atrial compliance and early diastolic dysfunction, but its role in pediatric CoA is underexplored. Methods The study was a multicenter, cross-sectional, observational study conducted at three tertiary hospitals in Vietnam. We enrolled 34 children with isolated CoA who underwent successful surgical repair, recruited between December 2022 and March 2025. LA volumes and strain, with LA reservoir strain (LASr) as the primary parameter, were assessed by two-dimensional speckle-tracking echocardiography. Values were compared with published pediatric reference data. Left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) were also measured. Results Despite preserved LVEF and normal anatomy, mean LASr was significantly reduced in the CoA group (37.6 ± 6.2%) compared to reference values (47.3%; p < 0.001). LAScd was also significantly reduced (23.4 ± 8.3%) compared to reference values (32.8%, p < 0.001). LA dilation was present in 18–56% of patients, but LASr was consistently impaired. Importantly, LASr did not significantly correlate with LVEF, GLS, blood pressure, or LA volume, suggesting it identifies an independent subclinical atrial dysfunction. Children with stage 1 hypertension had significantly lower LASr and larger LA volume. Conclusions Subclinical left atrial dysfunction is common in children after successful CoA repair, even in the absence of residual obstruction or systolic impairment. Measuring LA strain may provide incremental value for early risk stratification and long-term follow-up in this population.